2008
DOI: 10.1042/bj20071488
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the expression of calcium-permeable TRPC3 and TRPC7 channels enhances constitutive secretion

Abstract: The hTRPC [human TRPC (canonical transient receptor potential)] family of non-selective cation channels is proposed to mediate calcium influx across the plasma membrane via PLC (phospholipase C)-coupled receptors. Heterologously expressed hTRPC3 and hTRPC7 have been localized at the cell surface; however, a large intracellular component has also been noted but not characterized. In the present study, we have investigated the intracellular pool in COS-7 cells and have shown co-localization with markers for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…ASM cells express a variety of TRPC channels, with TRPC3 being particularly important for modulating Ca 2+ entry and in airway responses to inflammation (Amrani, 2007; Sweeney et al, 2002; Vohra et al, 2013; White et al, 2006). In non-neuronal cells, TRPC3 regulates secretion (Kim et al, 2011; Lavender et al, 2008). In a recent study, using DNA constructs to produce GFP-tagged BDNF, and real-time fluorescence imaging, we showed that vesicular BDNF release occurs in human ASM cells, and is regulated by TRPC3 (Vohra et al, 2013).…”
Section: Bdnf In the Lungmentioning
confidence: 99%
“…ASM cells express a variety of TRPC channels, with TRPC3 being particularly important for modulating Ca 2+ entry and in airway responses to inflammation (Amrani, 2007; Sweeney et al, 2002; Vohra et al, 2013; White et al, 2006). In non-neuronal cells, TRPC3 regulates secretion (Kim et al, 2011; Lavender et al, 2008). In a recent study, using DNA constructs to produce GFP-tagged BDNF, and real-time fluorescence imaging, we showed that vesicular BDNF release occurs in human ASM cells, and is regulated by TRPC3 (Vohra et al, 2013).…”
Section: Bdnf In the Lungmentioning
confidence: 99%
“…Although activation of many other vesicular TRPs (Fig. 1) has not been reported, some of them, for example, TRPC3 and TRPC7, have been shown to actively participate in trafficking/exocytosis (Lavender et al. 2008).…”
Section: Trp Channels In the Biosynthetic/secretory Pathwaymentioning
confidence: 99%
“…Relevant to airway disease, inflammatory cytokines such as TNFα increase TRPC3 expression [32, 33] while BDNF modulates TRPC3 function in human ASM [6]. In non-neuronal cells, [34, 35] TRPC3 has been shown to regulate secretion, but its non-SOCE role in ASM is not known. Accordingly, in the present study, we hypothesized that TRPC3 is important in BDNF secretion by ASM, and tested this hypothesis in human ASM in the context of enhanced BDNF secretion in the presence of inflammation.…”
Section: Introductionmentioning
confidence: 99%